(Neo-)Bogomil Legends: The Gnosticizing Bogomils of the Twentieth-Century Balkans. (16th November 2018) - Burns, Dylan; Radulović, Nemanja
Abstract : This contribution examines two modern, "Neo-Bogomil" groups: the Universal White Brotherhood (Bulgaria), and the Balkan Bogomil Center (Croatia). Both of these groups claim not only the authority of Bogomilism but ancient "Gnosticism, " articulating these dualist heresies in terms of Theosophy as well as South-Eastern European religious and ethnic-national identities formulated in the later nineteenth century.